Rural Food Markets and Child Nutrition. (3rd September 2019) - Headey, Derek; Hirvonen, Kalle; Hoddinott, John; Stifel, David
Abstract: Child dietary diversity is poor in much of rural Africa and developing Asia, prompting significant efforts to leverage agriculture to improve diets. However, growing recognition that even very poor rural households rely on markets to satisfy their demand for nutrient‐rich non‐staple foods warrants a much better understanding of how rural markets vary in their diversity, competitiveness, frequency and food affordability, and how such characteristics are associated with diets. This article addresses these questions using data from rural Ethiopia. Deploying a novel market survey in conjunction with an information‐rich household survey, we find that children in proximity to markets that sell more non‐staple food groups have more diverse diets. However, the association is small in absolute terms; moving from three non‐staple food groups in the market to six is associated with an increase in the number of non‐staple food groups consumed by ∼0.27 and the likelihood of consumption of any non‐staple food group by 10 percentage points. These associations are similar in magnitude to those describing the relationship between dietary diversity and household production diversity; moreover, for some food groups, notably dairy, we find that household and community production of that food is especially important. These modest associations may reflect several specific features of our sample which is situated in very poor, food‐insecure localities where even the relatively better off are poor in absolute terms and where, by international standards, relative prices for non‐staple foods are very high.